2019
DOI: 10.1080/10447318.2019.1699744
|View full text |Cite
|
Sign up to set email alerts
|

Who Do You Prefer? The Effect of Age, Gender and Role on Users’ First Impressions of Embodied Conversational Agents in eHealth

Abstract: Embodied conversational agents may be used to engage users in adopting eHealth applications. The aim of this research is to investigate which design features establish a positive first impression of an agent in this context. A set of eight static agent images, different in age, gender and role, were subjected to testing in an online questionnaire. Respondents (n = 155) selected their preferred design and rated the characteristicsfriendliness, expertise, reliability, involvement and authorityand the likeliness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 41 publications
0
59
0
Order By: Relevance
“…Although research on short-term interaction with an agent indicates that an agent’s appearance, including clothing [ 18 ], racial concordance with the user [ 30 , 31 ], and similarity with the user [ 30 , 32 ], could affect users’ perceptions of the agent, to the best of our knowledge there is no research on agent authority after short interaction in particular. From a previous study [ 16 ], we see that at first glance, static images of male and older agents are indeed seen as more authoritative than female and young agents, respectively. In addition, the study shows that the differences found in authority are often higher compared with differences found for other characteristics tested, which could explain why the difference in authority level is still present after short interaction.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Although research on short-term interaction with an agent indicates that an agent’s appearance, including clothing [ 18 ], racial concordance with the user [ 30 , 31 ], and similarity with the user [ 30 , 32 ], could affect users’ perceptions of the agent, to the best of our knowledge there is no research on agent authority after short interaction in particular. From a previous study [ 16 ], we see that at first glance, static images of male and older agents are indeed seen as more authoritative than female and young agents, respectively. In addition, the study shows that the differences found in authority are often higher compared with differences found for other characteristics tested, which could explain why the difference in authority level is still present after short interaction.…”
Section: Discussionmentioning
confidence: 79%
“…But research shows that in human-human interaction, first impressions, formed within milliseconds [ 28 ], are difficult to lose. Therefore, we assumed that the differences in perceptions of characteristics of a static image of a young female agent and an older male agent, as found in a previous study [ 16 ], would still be present after a short interaction with these agents. An explanation for this inconsistency could be that impressions in human-agent interaction differ from impressions in human-human interaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations